Inheritance of resistance to the Dectes stem borer, Dectes texanus LeConte (Coleoptera: Cerambycidae), in soybean plant introduction PI165673 - Aguirre-Rojas, Lina Maria (Kansas State University, 2013)
The Dectes stem borer, Dectes texanus LeConte, is a pest of soybean, Glycine max (L.) Merrill, in North America. Larval feeding weakens plant stems, triggering lodging of the infested plants and causing significant yield losses. D. texanus infestations in soybean fields are increasing across Kansas and other states, necessitating the development of effective tactics to control this pest. The use of D. texanus -resistant soybean cultivars is a desirable strategy to control this pest since cultural and chemical control options are lacking. In previous studies, the soybean plant introduction PI165673 was identified to be resistant to D. texanus. The objective of this research was to determine the inheritance of resistance to D. texanus in PI165673. F[subscript]2 progeny plants from crosses between the D. texanus susceptible genotypes KS5004N and K07-1544, and the resistant genotype PI165673 were tested in the field for resistance to D. texanus in 2011. Seeds from the cross K07-1544/PI165673 were advanced to the F[subscript]3 generation, and F[subscript]2:3 families were tested in the field for resistance to D. texanus in 2012. At 20 d after infestation with adults, the numbers of oviposition punctures and larvae on each plant were counted to estimate the oviposition puncture per larvae resistance ratio. Segregation for resistance to D. texanus and heritability estimates in the F[subscript]2 and F[subscript]2:3 populations indicated that resistance is controlled by more than one gene. Thirteen F[subscript]2:3 families had a higher (more resistant) resistance ratio than the susceptible parent K07-1544. Mean head capsule widths of larvae collected from K07-1544 and PI165673 plants in 2012 were similar, as was the percentage of larvae per larval instar. According to heritability estimates for each phenotypic trait, progress in breeding for D. texanus resistance using PI165673 will benefit from marker assisted selection. Identification of additional sources of D. texanus resistance besides that in PI165673 is needed to slow larval growth in the stem.
Keywords: Dectes texanus; Soybean; Soybean resistance to insects; Agriculture, General (0473); Entomology (0353)